Sagalassos VI : geo- and bio-archaeology at Sagalassos and in its territory - Degryse, Patrick; Waelkens, Marc (Sagalassos., 2008)
Since 1990, the ancient city of Sagalassos in southwestern Turkey has been the focus of an interdisciplinary archaeological research project coordinated by the Katholieke Universiteit Leuven. The papers collected in this volume reveal how the meticulous systematic and interdisciplinary reconstruction of the ecology and economy of the site and its territory has enhanced our understanding of the ancient settlement and its inhabitants beyond the traditional aspects of classical archaeology in Asia Minor. Highlighting geo-archaeological, archaeometrical, and bio-archaeological work performed withi.